Catalytic anode and method for electrolytic chlorine production

By using the catalyst layer of cobalt oxide crystal particles and antimony tin oxide matrix in the electrolytic chlorine production system, the problems of high cost and insufficient durability of precious metals are solved, and the efficient and low-cost electrolytic chlorine production reaction is achieved, which extends the anode Lifespan and reduce overpotential.

CN119162614APending Publication Date: 2024-12-20INFINEUM INT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410794103.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The precious metals of catalytic anode in the existing electrolytic chlorine production system are cost-effective and have insufficient durability and conductivity, resulting in increased efficiency loss and overpotential, affecting the efficiency and life of long-term operation.

Method used

A conductive metallurgical catalyst layer composed of cobalt oxide crystal particles is used to combine an oxide matrix of antimony and tin, and prepared under specific process conditions to form a catalytic anode with high selectivity and durability, avoiding excessive use of precious metals.

Benefits of technology

It realizes efficient electrolytic chlorine production reaction, reduces the overpotential, extends the working life of the anode, significantly reduces the cost, and improves the conductivity and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162614A_ABST
    Figure CN119162614A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytic anode for an electrolytic chlorine production system. The electrolytic chlorine production system generates chlorine from an aqueous solution through a chlorine evolution reaction. These anodes include an electrically conductive metallurgical catalyst layer substantially comprising crystalline cobalt oxide particles in a matrix of defined stoichiometric tin and antimony. The desired characteristics of such a metallurgical layer can be achieved by a production process employing specific control of reactants and process conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalytic anode for an electrolytic chlorine production system, wherein chlorine gas is generated from an aqueous solution containing chloride ions by a chlorine evolution reaction. Such chlorine production systems are particularly useful for industrial treatment and purification of wastewater, such as ballast water treatment systems and industrial water. They can also be used in particular for the industrial production of chlorine gas in chlor-alkali processes. Background Art

[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry that can be used both for large-scale production of chlorine for collection and for the generation of chlorine gas for immediate use. The chlor-alkali process generates chlorine gas and sodium hydroxide by electrolysis of an aqueous sodium chloride solution; the products are recovered and put into subsequent industrial use. Chlorine gas is also an effective biocide, so electrochlorination systems are also used independently for water purification based on the in-situ generation of chlorinated water and its immediate biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which is deployed in various occasions, such as industrial wastewater and general water sanitation. In addition, ships are increasingly carrying onboard ballast water treatment systems to treat water in ballast tanks before discharge. Ships sailing long distances are likely to introduce alien aquatic organisms into local ecosystems by discharging ballast water obtained at a distance. Invasive alien species can have a considerable impact on the balance of local ecosystems. Electrochlorination systems driven by generators on board provide an effective and immediate solution for treating such water before discharge.

[0003] The effective industrial application of electrolytic chlorine production systems and methods depends on electrolytic cells that can operate efficiently for a long time. In order to promote the generation of chlorine at the anode, it is common in the art to configure a catalytic coating on the surface of the anode facing the electrolyte to catalyze the chlorine evolution reaction. Such a catalytic coating usually contains a significant amount of one or more precious metals, of which iridium and ruthenium are the most commonly used, thereby significantly increasing the cost and complexity of anode manufacturing. There is still a continuous need in the art for a novel catalytic anode that can more cost-effectively meet various technical considerations related to industrial or municipal electrolytic chlorine production environments.

[0004] When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.

[0005] First, the selected catalyst must be sufficiently selective for the chlorine evolution reaction to reduce the efficiency loss caused by the competing oxygen evolution reaction that may otherwise also be caused by the electrolytic separation of water in aqueous solution at the anode. Second, the catalytic coating must be sufficiently durable to withstand long-term operation and acidification of the electrolyte that may occur with electrolytic chlorine production. Third, the anode coating should have a high conductivity to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolyzer. In practice, a certain degree of overpotential is usually evident in the electrolyzer due to efficiency losses; however, a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential during long-term operation provides a relevant measure of electrode durability and effective life.

[0006] The physical durability of the catalytic coating on the anode can be assessed by its performance in long-term tests and by examination of its morphology, most suitably by scanning electron microscopy. In fact, catalytic anode coatings in the art typically exhibit an outer surface morphology similar to that of a dry lake bed, with Figure 1 The appearance of finely-deposited sediments widely interrupted by characteristic "mud cracks" is shown in Figure 1. These cracks provide weak points in the catalyst layer and allow electrolyte and reactive species to penetrate downward toward the anode substrate, resulting in a degradation process that weakens the adhesion of the catalyst to the substrate and corrodes the exposed composition. This typically results in a loss of electrical efficiency (e.g., as evidenced by an increase in overpotential) and a loss of catalytic activity and a reduction in the effective life of the anode, resulting in expensive replacement. Summary of the invention

[0007] The catalytic anode of the first aspect of the invention provides a favorable balance of properties that solves these technical requirements of such anodes while avoiding the need for expensive precious metals, especially iridium, and can be obtained by the method of the second aspect of the invention. In particular, the catalyst-coated anode structure defined in the first aspect of the invention exhibits high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of working life, and improved tolerance to acids formed during operation. They also have high anode conductivity so as to maintain efficient electrical operation without excessive overpotential during long operation periods.

[0008] These advantages of the first aspect of the invention derive from the deployment of a conductive metallurgical catalyst layer covering the electrolyte-facing surface of the anode, the catalyst layer comprising a catalyst consisting essentially of a metallurgical catalyst having the formula Co in a defined crystalline matrix of oxides of antimony and tin. 3 O 4 Cobalt oxide crystal particles composed of crystalline cobalt oxide.

[0009] The characteristic morphology and chemical composition of this metallurgical catalyst layer is best achieved by a preparation method that employs controlled reactants and process conditions as further defined in the second aspect of the invention.

[0010] The present invention thus provides in a first aspect a catalytic anode structure for an electrolytic chlorine production system comprising a conductive solid substrate covered on the surface of the substrate facing the electrolyte with a conductive metallurgical catalyst layer comprising a catalyst having a chemical formula Co in a crystalline matrix of antimony and tin oxides. 3 O 4 cobalt oxide crystalline particles composed of crystalline cobalt oxide;

[0011] wherein the cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer; and wherein the overall metal stoichiometry of the total amount of cobalt: antimony and tin in the metallurgical catalyst layer is in the range of 2:1 to 9:1.

[0012] In the anode of the first aspect, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, and in particular, preferably further comprises ruthenium or an oxide thereof.

[0013] Within this specification, the term "atomic % of the total metal atomic content" with respect to a specified metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, and regardless of whether such metal element is present in elemental form or in the form of a compound.

[0014] Within this specification, the term "overall metal stoichiometry" for a particular metal element refers to the stoichiometric ratio of all atoms of those metal elements present in the composite metallurgical layer (or other composition, where applicable), whether those metal elements are present in elemental form or in compound form. For example, in a structure containing 15 atomic % antimony and 15 atomic % tin in pure elemental form, the overall metal stoichiometry of Sb:Sn is 15:15 or 1:1; and in a structure containing 15 atomic % antimony in the form of elemental antimony, 15 atomic % elemental tin and an additional 15 atomic % tin compounded in the form of an oxide, the overall metal stoichiometry of Sb:Sn is 15:(15+15) or 1:2.

[0015] In a preferred embodiment of the first aspect, the catalytic anode structure consists of an electrically conductive solid substrate covered with an electrically conductive metallurgical catalyst layer as defined above on its surface facing the electrolyte. In this embodiment, the catalyst layer is directly adjacent to the substrate.

[0016] In an alternative preferred embodiment of the first aspect, the catalytic anode structure comprises a conductive solid substrate covered on its surface facing the electrolyte with a metallurgical interlayer and a conductive metallurgical catalyst layer as defined above. In this alternative embodiment, the interlayer is directly adjacent to the substrate and the catalyst composition covers the interlayer to provide a catalytic surface layer. The preferred interlayer in this embodiment is a dimensionally stable anode composition, most preferably the interlayer composition described below.

[0017] The outer surface of the metallurgical catalyst layer according to the composition defined above has a favourable morphology of a continuous coating of aggregated cobalt oxide particles embedded in a matrix of tin and antimony oxides.

[0018] Within this specification, the term "morphology" is used to refer to the three-dimensional structure and appearance of the material in question. Morphology can be most effectively identified by scanning electron microscopy as described below, which provides three-dimensional imaging of material surfaces in a manner that allows direct visual identification of material structure and appearance.

[0019] Also within this specification, the term "continuous coating" is used to denote a coating that completely covers the underlying electrode material. Preferably, such a continuous coating is not interrupted by significant cracks or other permeable discontinuities that diminish its integrity. In particular, the continuous coating of the metallurgical catalyst layer of the present invention advantageously does not exhibit the extensive "mud crack" deposit morphology of conventional catalytic coatings used for electrolytic chlorine production, but rather provides a continuous surface covering or layer consisting of a three-dimensional matrix of aggregated particles visible under scanning electron microscopy.

[0020] The present invention is based in part on the following discovery: by a catalyst composition based essentially on cobalt oxide, an anode structure having excellent properties for obtaining a CER reaction in the electrolysis of chlorine can be advantageously obtained. The resulting metallurgical catalyst layer on the anode provides the anode with excellent durability in terms of working life, and provides favorable catalytic activity and selectivity for the chlorine evolution reaction. The metallurgical catalyst layer also provides the anode with high acid corrosion resistance and high electrical conductivity, resulting in high electrical efficiency and long-term operation performance at low overpotential. The use of a catalyst composition based primarily on cobalt oxide rather than a larger amount of precious metals also enables this anode performance to be achieved at a significantly lower cost than conventional catalytic anodes based on iridium and / or ruthenium as the main components.

[0021] In particular, the cobalt oxide crystalline particles serve as the essential catalytic species of the metallurgical catalyst layer and provide highly selective catalysis for CER reactions at a significantly lower cost than precious metal-based catalyst compositions (such as iridium-based compositions). Although the basic cobalt oxide catalyst of the present invention can be supplemented with catalytic precious metal oxides, cobalt should be present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer, thus representing the major catalytic species in the catalyst composition. This use of cobalt oxide as the major catalyst species is achieved through its combined use with a defined antimony and tin oxide matrix in the catalyst layer, which combination helps to provide a highly selective, durable and efficient cobalt oxide-based catalytic anode for CER with the improved property balance described above.

[0022] Aggregated crystalline particles on the outer surface of the metallurgical catalyst layer are also necessary to provide a highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transfer limitations of conventional lakebed deposited catalyst layers, enabling the catalytic anode of the first aspect of the present invention to operate the chlorine evolution reaction at a higher efficiency and contributing to the various advantages of the present invention.

[0023] The efficiency advantage of the catalytic anode of the present invention in the chlorine evolution reaction can be particularly demonstrated with aqueous chloride ion solutions (such as brine) with low salt content. The improved efficiency at low salt content provides an electrode with broad applicability to water treatment, for example, in addition to wastewater treatment and other chlorination applications, it is also suitable for municipal water applications or for treating drinking water. The improved efficiency also leads to lower levels of unwanted electrolysis byproducts such as chlorate and perchlorate ions.

[0024] In a preferred form of the catalytic anode of the first aspect, the catalyst composition does not contain titanium or a compound thereof. Such a titanium-free catalyst composition provides the resulting anode with the additional advantage of being highly suitable for current-reversal cells. Current reversal has become a maintenance-friendly means for removing deposits of metals such as calcium and magnesium, which otherwise may accumulate on the cathode during long electrolytic operations, especially for municipal water or residential water, such as the treatment of swimming pool water, especially at low salt content. However, current reversal in the electrolytic cell conventionally causes faster degradation and damage of the anode catalytic coating, due to large fluctuations in pH occurring at the electrode surface, especially within the cracked surface of the "mud crack" catalyst, where the electrolyte may be depleted of brine (brine depleted) and the competitive water decomposition reaction becomes more dominant. The titanium present in the coating is easily dissolved in this environment, resulting in weakening of the catalytic coating on the substrate and rapid degradation of the coating and performance. The anode provided by the present invention can omit the presence of titanium in the catalyst composition and thereby avoid such degradation due to the high efficiency and cobalt content of its catalyst composition, thereby making the anode life longer, especially in a current reversal environment.

[0025] Such a titanium-free catalyst composition also provides the resulting anode with the additional advantage of being more resilient in high salt content processes, i.e., chlor-alkali processes. Typically, a chlor-alkali electrolyzer has a Teflon or similar membrane placed between the cathode and the anode. The caustic solution in the electrolyzer can cause holes to form in the membrane so that the caustic can reach the anode and cause titanium corrosion and consumption. The anode provided by the present invention can omit the presence of titanium in the catalyst composition and thus avoid such degradation due to the high efficiency and cobalt content of its catalyst composition, thereby making the anode life longer in such an environment.

[0026] The formation of the catalytic anode structure of the first aspect of the invention is best achieved by adding the catalyst composition under process conditions that ideally favor the formation of a catalyst layer of the correct composition on the anode surface and impart the desired morphology of the metallurgical catalyst layer.

[0027] The present invention therefore provides in a second aspect a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:

[0028] a) preparing or obtaining a conductive solid substrate;

[0029] b) applying to the surface of the substrate facing the electrolyte a conductive metallurgical catalyst precursor composition comprising a catalyst having a chemical formula of Co dispersed in a mixture of antimony and tin compounds 3 O 4a composition of crystalline cobalt oxide particles composed of crystalline cobalt oxide ...

[0030] wherein the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and

[0031] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

[0032] The method of the second aspect is particularly characterized in that it uses specific starting metallurgical compositions and preparation conditions to produce the anode structure of the first aspect.

[0033] In a preferred embodiment of the second aspect, the method consists of steps (a) and (b) to obtain a catalytic anode structure consisting of a conductive solid substrate covered with a conductive metallurgical catalyst layer as defined above on its surface facing the electrolyte. In this embodiment, the catalyst layer is directly adjacent to the substrate.

[0034] In an alternative embodiment of the second aspect, between process steps (a) and (b), an additional metallurgical composition (c) may be applied to obtain a catalytic anode structure comprising a conductive solid substrate, covered on the surface of the conductive solid substrate facing the electrolyte with a metallurgical interlayer (derived from the additional metallurgical composition (c)) and a conductive metallurgical catalyst layer as defined above. In this alternative embodiment, the interlayer is directly adjacent to the substrate and the catalyst composition covers the interlayer to provide a catalytic surface layer.

[0035] During application of step (b), the specified process solvents and subsequent drying and heat treatment of the resulting structure contribute to the formation of a favorable morphology and composition of the resulting metallurgical catalyst layer on the anode of the present invention.

[0036] It has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical catalyst layer, particularly by favoring a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, a second aspect of the invention preferably has a final heat treatment in the range of 450 to 550°C, particularly an optimal final heat treatment at 500°C, where higher selectivity and durability to the chlorine evolution reaction are observed.

[0037] The second aspect of the present invention also importantly requires that the metallurgical composition is applied in step (b) using a specified process solvent, which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. For the solubility of the starting compound used in the method of the second aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly conducive to the presence of aggregated particle morphology without cracks that weaken integrity. This ability to control the morphology of the layer is particularly attributed to the selection of the alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a ratio of 85:15 (isopropanol: water).

[0038] In a preferred embodiment of the method, applying the metallurgical catalyst precursor composition to a substrate that is heated to a specified temperature range of 55-200°C during the application process (preferably heated to this temperature range throughout the application process) has been found to enhance the formation of the desired metallurgical catalyst layer on the anode.

[0039] Drying of the resulting structure at the same temperature range of 55-200°C has also been found to enhance the formation of the desired metallurgical catalyst layer, particularly by facilitating the formation of the desired morphology of a continuous layer uninterrupted by mud cracks or other significant permeability discontinuities.

[0040] Further aspects of the invention are also described herein and include:

[0041] An electrolytic chlorine production system comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect; and

[0042] An electrolytic method for catalyzing the evolution of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect, wherein chlorine gas is evolved from the aqueous solution at the anode.

[0043] In a preferred aspect of the electrolysis process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an alternative preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.

[0044] The present invention will now be described in more detail as follows: BRIEF DESCRIPTION OF THE DRAWINGS

[0045] This application includes the following drawings:

[0046] Figure 1 : Lake bed morphology of conventional catalyst layer with extensive “mud cracks”;

[0047] Figure 2 : The aggregated microparticle morphology of one embodiment of the present invention;

[0048] Figure 3 : Anode life improvement resulting from a combination of cobalt, tin and antimony in defined stoichiometric amounts in a catalyst precursor composition, the figure showing the life improvement resulting from the preferred inclusion of tin and antimony in defined stoichiometric amounts in the catalyst precursor composition of the process; and

[0049] Figure 4 : Improved anode life resulting from the inclusion of tin and antimony in defined stoichiometric amounts in the catalyst precursor composition of the process;

[0050] Figure 5 : Improvement in anode CER efficiency resulting from the inclusion of tin and antimony in defined stoichiometric amounts in the catalyst precursor composition of the process, the figure showing the chlorine evolution efficiency (CER) of the electrode of the present invention having various Sn / Sb stoichiometric ratios in the preferred catalyst precursor composition; DETAILED DESCRIPTION

[0051] First Aspect of the Invention (Catalytic Anode)

[0052] The catalytic anode structure of the first aspect comprises a conductive solid substrate covered on its surface facing the electrolyte with a conductive metallurgical catalyst layer comprising a catalyst having a chemical formula of Co in a crystalline matrix of antimony and tin oxides. 3 O 4 wherein the cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer; and wherein the overall metal stoichiometric ratio of cobalt: antimony and tin in the metallurgical catalyst layer is in the range of 2:1 to 9:1.

[0053] The anode structure of the first aspect of the present invention is obtainable by the method of the second aspect of the present invention, and is preferably obtained by the method of the second aspect of the present invention.

[0054] The anode structure of the first aspect, especially when prepared according to the method of the second aspect, is advantageously characterized in that the outer surface of the metallurgical catalyst layer has the morphology of a continuous coating of aggregated particles. The presence of occasional cracks or other surface discontinuities or fault lines is not excluded, wherein these defects do not penetrate into the depth of the catalyst layer composition or expose the underlying substrate to electrolyte corrosion. However, preferably, the metallurgical catalyst layer of the anode structure of the first aspect has an outer surface morphology of a continuous uncracked coating of aggregated particles.

[0055] The favorable aggregated particulate morphology of the outer surface of the metallurgical catalyst layer contrasts with the extensively cracked, deposit-like surface morphology of conventional catalytic anodes and can be best visualized by examination under scanning electron microscopy as shown in the accompanying figures. In each case, the JSM-IT500 InTouchScope TM Scanning electron microscope instrument, electron micrographs were obtained using the settings specified in the legends to the relevant figures.

[0056] exist Figure 1 Scanning electron microscopy of the external surface morphology of a conventional catalytic anode used for electrolytic chlorine production shows a characteristic "mud crack" appearance, with extensive deep cracks radiating through a sediment-like surface coating. Such morphology renders the catalytic surface susceptible to chemical attack and weakens its structural integrity, reducing its life and usefulness.

[0057] On the contrary, Figure 2 , scanning electron microscopy shows the surface of a preferred catalytic anode of the first aspect, with a continuous uncracked surface layer and aggregated particulate morphology visible at the magnification shown.

[0058] An important element of the anode structure of the first aspect is the presence of cobalt oxide in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer. The anode of the present invention provides a means for configuring a high content of cobalt oxide-based catalyst in the anode in a form that is highly selective for electrolytic chlorine production, which provides excellent durability, high acid corrosion resistance and high conductivity in terms of the working life of the catalyst on the anode substrate, resulting in high electrical efficiency and operating performance at low overpotentials. The use of a catalyst composition that is largely based on cobalt oxide as the main catalytic component rather than precious metals also enables this anode performance to be achieved at a significantly lower cost than conventional precious metal-based catalysts (such as iridium-based catalytic anodes).

[0059] Preferably, in the anode structure of the first aspect, cobalt oxide is present in the highest amount practicable to maximize its catalytic effect while obtaining the other advantages of the invention. Therefore, preferably, cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the metallurgical catalyst layer, more preferably in an amount of at least 20 atomic % of the total metal atomic content of the metallurgical catalyst layer. Even more preferably, cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the metallurgical catalyst layer, most preferably in an amount of at least 40 atomic % of the total metal atomic content of the metallurgical catalyst layer. Ideally, cobalt is present in an amount ranging from 50 to 80 atomic % of the total metal atomic content of the metallurgical catalyst layer, preferably in an amount ranging from 60 to 75 atomic % of the total metal atomic content of the metallurgical catalyst layer. Such a cobalt content is advantageously achieved by preparing an anode structure according to the method of the second aspect of the invention.

[0060] The individual metal contents and overall metal stoichiometry of the metallurgical catalyst layer may be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectrometry) to determine the compositional characteristics of the present invention.

[0061] In the anode structure of the first aspect, it is preferred that the cobalt oxide crystalline particles in the catalyst composition are composed of a material having the chemical formula Co 3 O 4 The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques. 3 O 4 The size of the crystalline particles can be determined by directly measuring their diameter in a transmission electron microscopy image, and is preferably 1 nm to 20 nm in diameter, more preferably 1 nm to 10 nm, and most preferably 3 to 7 nm in diameter.

[0062] In the anode of the first aspect, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, in particular ruthenium or its oxide. In keeping with the objectives of the present invention, the amount of any noble metal included should be sufficiently small so that the cobalt content of the metallurgical catalyst layer does not drop below the level specified in the present invention, and the amount of the noble metal should preferably not exceed 10 atomic % of the total metal atomic content of the metallurgical catalyst layer, more preferably not more than 5 atomic %.

[0063] In a more preferred embodiment, the cobalt oxide crystalline particles in the catalyst composition consist essentially of the chemical formula Co 3 O 4The catalyst composition may be a crystalline cobalt oxide having a composition of at least about 100 μm and further comprising ruthenium in an amount of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is present as a surface decoration on the crystalline particles. In this latter embodiment of the anode, the crystalline cobalt oxide particles in the catalyst composition may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.

[0064] The limited amount of ruthenium combined with the cobalt oxide crystalline particles in the catalyst composition provided in these embodiments provides the property of the metallurgical catalyst layer on the anode to be further improved, most especially the selectivity of the catalyst to the chlorine evolution reaction and the advantage of improving the durability (particularly in terms of operating life) of the anode. At least in the case of being incorporated into the lattice of cobalt oxide, ruthenium can exist in the form of oxide compounds or in the form of metallic elements. The ruthenium combined with the cobalt oxide catalyst in these embodiments may exist in an overall non-stoichiometric ratio, close to a mixture of elemental ruthenium and oxide-bound ruthenium.

[0065] However, it has been found that exceeding the upper limit of 5 atomic % for the ruthenium content in the crystalline particles of the catalyst composition leads to a reduction in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by a reduction in the low salt efficiency. Therefore, the ruthenium content associated with the cobalt oxide catalytic particles should be limited to the specified level, and further increasing the ruthenium content is not advantageous under any expectation of further improvement.

[0066] In all of the above embodiments of the anode of the first aspect, the metallurgical catalyst layer comprises crystalline particles of cobalt oxide distributed on the upper surface of the anode structure. Preferably, the catalyst composition consists essentially of crystalline particles of cobalt oxide distributed in a crystalline matrix of antimony and tin oxides, wherein the matrix does not contain a significant amount or any amount of precious metal oxides other than those provided herein with respect to the present invention, such as palladium or iridium.

[0067] In particular, in all embodiments of the anode, the catalyst composition consists essentially of crystalline particles of cobalt oxide within a crystalline matrix of antimony and tin oxides; such catalyst composition is present on the surface of the anode facing the electrolyte.

[0068] It has been surprisingly found that this overall ratio of cobalt: antimony and tin in the metallurgical catalyst layer provides advantageous properties. By keeping it within a defined range, the durability of the catalytic anode is improved, as evidenced by an increase in its effective working life. This increase in life provides very advantageous properties for the anode of the first aspect.

[0069] In particular, in all embodiments of the anode, the catalyst composition is included in cobalt oxide crystalline particles in a crystalline matrix of antimony and tin oxides, and is preferably substantially composed of cobalt oxide crystalline particles in a crystalline matrix of antimony and tin oxides. Preferably, the cobalt in the metallurgical catalyst layer: the overall metal stoichiometric ratio of the total amount of antimony and tin is in the range of 2:1 to 9:1. More preferably, the cobalt in the metallurgical catalyst layer: the overall metal stoichiometric ratio of the total amount of antimony and tin is in the range of 2.5:1 to 6:1, most preferably in the range of 3:1 to 5:1. Optimally, the cobalt in the metallurgical catalyst layer: the overall metal stoichiometric ratio of the total amount of antimony and tin is in the range of 3:1 to 4:1. It has been surprisingly found that the cobalt in the metallurgical catalyst layer: the overall metal stoichiometric ratio of the total amount of antimony and tin provides favorable performance. By keeping this ratio within the above-mentioned general range, as demonstrated by the increase in its effective working life, the durability of the catalytic anode is improved. This increase in life provides very favorable performance for the anode of the first aspect.

[0070] On the anode, it is preferred that the antimony and tin compounds acting as a matrix in the catalyst composition are present in an amount to provide the metallurgical catalyst layer with an overall metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:100. In this regard, it has been further surprisingly found that the overall metal stoichiometry of antimony:tin in the metallurgical catalyst layer provides a further contribution to achieving optimal anode performance. Maintaining this overall stoichiometry within the above range provides a further improved operating life for the anode and also improves the CER efficiency of the electrolyzer as evidenced by the Faraday efficiency.

[0071] Preferably, the antimony and tin compounds are present in an amount to provide the metallurgical catalyst layer with a preferred overall metal stoichiometric ratio of antimony:tin in the range of 1:25 to 1:100, most preferably in the range of 1:50 to 1:84. This ratio may best be in the range of 1:50 to 1:85, with excellent embodiments being 1:75 and 1:84.

[0072] In each of the above embodiments of the anode structure, it is preferred that the metallurgical catalyst layer further comprises at least one palladium compound. Its amount provides a total palladium content of up to 7 atomic % based on the total metal atomic content of the composite metallurgical layer. It is preferred that a limited amount of palladium is introduced into the layer by including one or more palladium-based compounds in the catalyst composition or by subsequent doping. As demonstrated by the improvement in low salt efficiency, palladium provides a further improvement in the efficiency of the chlorine evolution reaction, particularly for water treatment applications.

[0073] However, the palladium content in the catalyst composition exceeding the upper limit of 7 atomic % does not bring further improvement in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by the lack of further improvement in low salt efficiency. Therefore, the palladium content combined with the cobalt oxide catalytic particles should be limited to a specified level to avoid unnecessary cost and complexity. Preferably, the total palladium content is at most 5 atomic %, more preferably at most 3% of the total metal atomic content of the composite metallurgical layer; and optimally, the total palladium content is at most 1.5% of the total metal atomic content of the composite metallurgical layer.

[0074] The anode of all embodiments of the first aspect is essentially composed of a conductive solid substrate, which is known in the art. Such a substrate is preferably essentially composed of valve metals such as titanium, zirconium, niobium and tantalum (and alloys / mixtures containing these metals), preferably titanium, and most preferably essentially composed of titanium. A mixture of valve metals may be present in the substrate. It may be further observed or produced as an artificial product under the conditions of anode manufacturing and use that the oxide of the valve metal is essentially present in the substrate, particularly at the surface of the substrate or at its interface with the metallurgical catalyst layer, and the substrate of the present invention does not exclude their presence, as long as they do not form the main constituent component of the substrate.

[0075] The anode substrate can be produced by conventional means in the art and can be purchased or manufactured to order and formed into any shape suitable for final use as an anode in an electrochemical cell or system. In particular, the substrate can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Depending on their design and arrangement, the substrate can be coated with a composite metallurgical layer on one or more sides.

[0076] In the anode of all embodiments of the first aspect, the distribution of the cobalt oxide-based catalyst composition extends through the depth of the metallurgical catalyst layer. The distribution of the metal elements in the thickness of the structure of the metallurgical catalyst layer according to the present invention can be visualized by imaging using a transmission electron microscope (TEM) according to the mapping technique TEM-EDS (transmission electron microscopy and energy dispersive X-ray spectroscopy).

[0077] Using TEM-EDS technology, the distribution of various basic constituent metals can be directly imaged, and their distribution within the thickness of the metallurgical catalyst layer is observed to confirm the presence of the anode structure of the present invention, especially when compared with the overall image obtained by HAADF (high angle annular dark field transmission electron microscopy). Using TEM-EDS mapping (mapping) technology, each metal element in the metallurgical catalyst layer can be visualized individually. In particular, cobalt oxide particles are easily observed in dense concentrations (coatings) on the outer surface of the layer, but cobalt is also visible in the entire depth of the layer at a lower density. Ruthenium present in the catalyst composition at a low content therefore appears in the surface region of the higher cobalt catalyst density on TEM-EDS at a lower density. Tin is distributed throughout the layer and is present in the antimony-tin matrix of the catalyst composition.

[0078] The distribution and concentration of metal elements throughout the metallurgical catalyst layer can also be quantitatively measured using TOF-SIMS (Time of Flight Secondary Ion Mass Spectrometry) technology. This technique is capable of mapping metal concentrations down through the depth of the metallurgical catalyst layer and can also confirm the presence of the structures of the present invention.

[0079] In the anode of the first aspect, it is preferred that the cobalt of the catalyst composition is distributed throughout the thickness of the metallurgical catalyst layer.

[0080] In a further enhanced embodiment of the anode of the first aspect, the metallurgical catalyst layer further comprises ruthenium oxide distributed throughout or substantially distributed throughout the catalyst layer. In particular, it is preferred that the ruthenium oxide is distributed in the catalyst matrix of the above-mentioned antimony and tin oxides. The inclusion of ruthenium oxide throughout or substantially distributed throughout the metallurgical catalyst layer further improves the conductivity of the layer and improves the low-salt efficiency of the anode, and also improves the long-term durability of the anode structure.

[0081] In a further preferred embodiment of the anode of the first aspect, an additional metallurgical layer ("interlayer") may be present directly on the anode substrate, thereby providing a foundation layer for the overlying catalyst composition.

[0082] In a preferred interlayer embodiment, ruthenium oxide can be advantageously applied as an intermediate layer (or "interlayer") between the anode substrate and the catalyst composition. This is preferably applied during the process of the method of the second aspect, and subsequent heat treatment of the resulting structure causes the ruthenium oxide interlayer to migrate throughout the catalyst layer, enhancing the conductive path through the catalyst layer and bringing other advantages identified above.

[0083] In another preferred interlayer embodiment, the interlayer composition may comprise a mixture of metal oxides, preferably those known in the art as dimensionally stable anode compositions. Such a mixture may comprise titanium oxide, tin oxide, and / or ruthenium oxide, and may form a discrete interlayer between the anode substrate and the metallurgical catalyst composition, thus acting as a structural base layer rather than a conventional catalyst layer.

[0084] In a more preferred form of the above-mentioned interlayer embodiment, the interlayer of the anode structure comprises titanium or one or more compounds thereof, or tantalum or one or more compounds thereof, or both. Such an interlayer provides a protective layer for the anode substrate, which is then covered with the metallurgical catalyst composition of the present invention. Optionally, an intermediate layer of ruthenium oxide may be applied between the interlayer comprising titanium and / or tantalum on the substrate and the metallurgical catalyst composition forming the outer layer of the anode structure.

[0085] In an alternative preferred embodiment, the anode has a single interlayer comprising ruthenium or one or more compounds thereof, preferably also titanium or one or more compounds thereof. Such an interlayer eliminates the need for a separate intermediate layer of ruthenium or a ruthenium compound, but rather includes the ruthenium or a ruthenium compound in an interlayer structure below the metallurgical catalyst composition forming the outer layer of the anode structure.

[0086] In another alternative embodiment, the anode structure interlayer comprises a limited amount of iridium or one or more compounds thereof, so that the content of iridium does not hinder the achievement of the overall object of the present invention. Thus, the anode structure comprises iridium, in the form of its oxide or other catalytically active species, in an amount that provides a total iridium content of at most 15 atomic % of the total metal atomic content of the metallurgical catalyst layer, preferably at most 5 atomic %. Iridium may be present in addition to the other interlayer metallurgies defined above, more particularly in addition to ruthenium or titanium or tantalum or mixtures thereof.

[0087] In the above-described sandwich anode structure, if a titanium, tantalum, ruthenium or iridium compound is present, it preferably comprises an oxide compound, and preferably consists of an oxide compound. Alternatively, the interlayer composition may comprise a mixture of metal oxides that migrate into or intermix with the overlying catalyst composition, thereby forming a composite metallurgical layer on the electrolyte-facing surface of the anode.

[0088] Such additional presence of a defined base composition, preferably comprising ruthenium, tin and / or titanium oxides, as a structural base layer of the overlying catalytic composition provides structural integrity to support the overlying cobalt-based catalyst composition.

[0089] The preferred embodiment of the structural base composition of this alternative interlayer embodiment of the anode of the first aspect comprises metal oxide compounds of ruthenium, tin and titanium, preferably consisting essentially of metal oxide compounds of ruthenium, tin and titanium. The combination of these three metals is important for obtaining the ideal form of the structural base composition in situ on the anode surface. Other metal oxides or other compounds may be present in addition, as long as they do not adversely affect the basic composition form, but most preferably, the structural base composition composition consists of metal oxide compounds of ruthenium, tin and titanium.

[0090] In particular, the specific combination of ruthenium, tin and titanium provides a base structure composition that exhibits a base morphology of aggregated particles interspersed with voids and is therefore also crack-free, providing a resilient base structure onto which the catalyst composition can be applied.

[0091] In addition, the specific combination of ruthenium, tin and titanium in the structural base composition provides improved durability for the anode of the first aspect of the invention compared to similar base compositions containing only ruthenium and titanium or only ruthenium and tin. In this regard, the combination of both tin and titanium with ruthenium provides improved anode life and improved mechanical adhesion for the anode of the invention and further contributes to the advantages of the invention.

[0092] The above-described embodiments of the first aspect of the invention may further comprise, in addition to the above-described features, one or more additional constituent elements for enhancing specific properties of the anode, provided that the overall advantages of the invention are still obtained. For example, in the anode structure of any of the foregoing embodiments, the catalyst composition may additionally comprise a catalytic noble metal (in addition to any palladium if palladium is present), preferably iridium, in the form of its oxide or other catalytically active species, in an amount that provides up to 15 atomic % of the total metal atomic content of the composition, preferably up to 5 atomic % of the total additional noble metal content, preferably iridium content. The optional presence of such small amounts of noble metals, particularly iridium, may be advantageous from the perspective of further enhancing the catalytic performance of the anode, but for the purposes of the present invention, should be limited to minimize the use of expensive noble metals and rely primarily on cobalt oxide for catalytic activity. Therefore, such amounts of noble metals are much lower than the amounts typically used when the catalyst composition is based on such metals.

[0093] Alternatively or additionally, the catalyst composition on the anode of all embodiments may further comprise at least one copper compound in an amount providing the catalyst composition with a total copper content of up to 10 atomic%, preferably up to 2 atomic%; or at least one aluminum compound in an amount providing the catalyst composition with a total aluminum content of up to 30 atomic%, preferably up to 20 atomic%; at least one nickel compound in an amount providing the layer with a total nickel content of up to 15 atomic%, preferably up to 10 atomic% of the total metal atomic content of the metallurgical catalyst layer; or more than one of these. The additional presence of copper or aluminum or nickel in the catalyst composition provides further improved catalyst selectivity for the chlorine evolution reaction, for example as measured by low salt efficiency. Preferably, copper and / or aluminum and / or nickel are introduced via the catalyst composition and are present in the catalyst composition, for example in the form of one or more oxide compounds.

[0094] The second aspect of the present invention (preparation method)

[0095] A second aspect provides a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:

[0096] a) preparing or obtaining a conductive solid substrate;

[0097] b) directly applying to the surface of the substrate facing the electrolyte a conductive metallurgical catalyst precursor composition comprising a catalyst having a chemical formula of Co dispersed in a mixture of antimony and tin compounds; 3 O 4 a composition of crystalline cobalt oxide particles composed of crystalline cobalt oxide ...

[0098] wherein the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and

[0099] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

[0100] The method of the second aspect of the invention results in a catalytic anode structure as defined under the first aspect of the invention and is the preferred method for preparing the anode of the first aspect.

[0101] In a first preferred embodiment of the process, the metallurgical catalyst precursor composition is applied in step (b) to the surface of the substrate facing the electrolyte, so as to obtain an anode in which the metallurgical catalyst composition is directly adjacent to the substrate.

[0102] In a second preferred embodiment of the method, a metallurgical base composition is applied directly to the electrolyte-facing surface of the substrate prior to step (b) to form a metallurgical interlayer directly adjacent to the substrate surface; and in step (b) a metallurgical catalyst precursor composition is applied to the outer surface of the metallurgical interlayer. In this embodiment, the metallurgical interlayer is preferably a dimensionally stable anode composition, more preferably one or more preferred types of interlayers described above with respect to the first aspect of the invention.

[0103] In the method of the second aspect, defined temperature conditions and process solvents are important to obtain the desired catalytic anode structure.

[0104] After drying in the method, the resulting dried structure is heat treated at a temperature of at least 450° C., preferably at a temperature in the range of 450 to 550° C. More preferably, the resulting dried structure is heat treated at a temperature in the range of 475 to 525° C., most preferably at 500° C.

[0105] The method of the present invention also requires applying the metallurgical composition in step (b) using a specified process solvent, which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15.

[0106] With respect to the solubility of the starting compounds used in the method of the second aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly helpful in obtaining an aggregated particle morphology without cracks that weaken the integrity. This ability to control the layer morphology is particularly due to the choice of alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a ratio of 85:15 (isopropanol:water).

[0107] Preferably, in the process of the present invention, the anodic substrate (a) is heated to a temperature in the range of 55-200°C during step (b), and the resulting structure is thereafter dried at a temperature in the same range. Preferably, the heating of the anodic substrate to this temperature range is carried out throughout step (b), and the resulting structure is thereafter dried at a temperature in the same range. Optimally, the substrate (a) is heated to a temperature of 100°C throughout step (b), and the resulting structure is thereafter dried at this temperature.

[0108] Furthermore, with respect to the second embodiment comprising forming the interlayer prior to step (b) of the method, the same heat treatment and defined process solvents may be used to apply the metallurgical base composition. During the application of step (b), the specified heating conditions of the substrate and the defined process solvents and the subsequent drying and heat treatment of the resulting structure contribute to the formation of the favorable morphology and composition of the resulting composite metallurgical layer on the anode of the present invention.

[0109] In particular, applying the catalyst composition to a substrate heated in accordance with the second aspect of the invention has been found to enhance the formation of the desired metallurgical catalyst layer on the anode. It has also been found, importantly, that drying of the resulting structure at the same temperature range enhances the formation of the desired metallurgical catalyst layer, particularly by favoring the formation of the desired morphology of a continuous layer that is not interrupted by mud cracks or other significant permeability discontinuities.

[0110] Likewise, it has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical catalyst layer, favoring a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, a second aspect of the invention preferably has a final heat treatment in the range of 450 to 550°C, especially an optimal final heat treatment at 500°C, where a higher selectivity for the chlorine evolution reaction and mechanical adhesion is observed.

[0111] The use of the above defined temperature conditions and process solvents in the method of the second aspect, combined with the defined metallurgical content of the starting composition, results in the formation of a metallurgical catalyst layer having the desired composition and morphology on the anode substrate, which is suitable for use as the anode of the first aspect.

[0112] In the method of the second aspect, the conductive metallurgical catalyst precursor composition comprises crystalline cobalt oxide particles of the type described above with respect to the first aspect.

[0113] In this regard, the cobalt oxide crystalline particles in the catalyst precursor composition are essentially composed of particles having the chemical formula Co 3 O 4 In one such embodiment, the cobalt oxide crystalline particles may be composed of a crystalline cobalt oxide having the formula Co 3 O 4 The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques.

[0114] In another more preferred embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of a material having the chemical formula Co 3 O 4In one embodiment, the catalyst precursor composition comprises a crystalline cobalt oxide having a composition of 100% by weight and further comprising ruthenium to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is present in the form of a surface decoration on the crystalline particles. In this latter embodiment, the crystalline cobalt oxide particles in the catalyst precursor composition may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.

[0115] The limited amount of ruthenium combined with the cobalt oxide crystalline particles in the catalyst precursor composition provided in these embodiments provides the advantage of further improving the properties of the metallurgical catalyst layer when applied to the anode in the method of the present invention, most especially by improving the selectivity of the catalyst to the chlorine evolution reaction and improving the durability of the anode, particularly in terms of operating life. At least in the case of being incorporated into the lattice of cobalt oxide, ruthenium can exist in the form of an oxide compound or in the form of a metallic element. The ruthenium combined with the cobalt oxide catalyst in these embodiments can exist in an overall non-stoichiometric ratio, close to a mixture of elemental ruthenium and oxide-bound ruthenium.

[0116] However, for the ruthenium content associated with the crystalline particles in the catalyst precursor composition, it has been found that exceeding the upper limit of 5% can lead to reduced efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by reduced low salt efficiency. Therefore, the ruthenium content associated with the cobalt oxide catalytic particles should be limited to the specified level, and further increasing the ruthenium content is not beneficial under any expectation of further improvement.

[0117] In all of the above embodiments, the catalyst precursor composition consists essentially of crystalline particles of cobalt oxide distributed in a mixture of other metal compounds comprising antimony and tin, which mixture, when applied by the method of the second aspect, produces a crystalline matrix of metal oxides of antimony and tin in the final catalyst composition of the anode of the invention. It is particularly preferred that these other metal compounds do not contain a significant amount or any amount of precious metal oxides other than those provided herein with respect to the present invention, such as palladium or iridium.

[0118] In this regard, the method of the second aspect is advantageously carried out using as the catalyst precursor a composition in which crystalline particles of cobalt oxide (as described above) are dispersed in a mixture of antimony and tin compounds, wherein the overall metal stoichiometry of cobalt: total amount of antimony and tin in the composition is in the range of 20:80 to 80:20. This combination of antimony and tin compounds in the composition, when applied by the method of the second aspect, produces a crystalline matrix of antimony and tin oxides in which the crystalline particles of cobalt oxide aggregate to give the desired morphology of the metallurgical catalyst layer.

[0119] In this preferred embodiment, it has also been found that, compared with the ratio outside the specified ratio range, the molar ratio of cobalt: antimony and tin total amount used in the metallurgical catalyst precursor composition provides the improved operation durability of the anode structure obtained by the method of the present invention, which is proved by maintaining a lower overpotential for a longer time. In addition, within the specified ratio range, the efficiency of the obtained catalytic anode to the chlorine evolution reaction is improved. In these respects, the overall metal stoichiometric ratio of cobalt: antimony and tin total amount of 30:70 to 80:20 is preferred, and the range of 60:40 to 40:60 is more preferred, and the ratio of 50:50 is most preferred and best, especially for obtaining the obtained anode with high CER efficiency and longer working life at low overpotential.

[0120] In the above preferred embodiments, it has also been found that the performance of the resulting anode can be further enhanced when prepared by the method of the second aspect using a metallurgical catalyst precursor composition: the overall metal stoichiometric ratio of the total amount of cobalt: antimony and tin is controlled as described above, and the antimony and tin compounds are present in an amount that provides an overall metal stoichiometric ratio of antimony: tin of at most 1: 10, preferably at most 1: 20 to the composition. In addition, controlling the antimony: tin ratio in the composition within this range by the method of the present invention results in an anode having further improved efficiency for the chlorine evolution reaction.

[0121] More preferably in this highly advantageous embodiment of the process, the overall metal stoichiometry of antimony:tin in the metallurgical catalyst precursor composition is at most 1:50, especially at most 1: 100. For achieving improved efficiency of the chlorine evolution reaction, the optimal overall metal stoichiometry of antimony:tin in the metallurgical catalyst precursor composition is 1:200.

[0122] Most preferably, the metallurgical catalyst precursor composition has both a preferred range of the ratio of cobalt: antimony and tin total amount, and a preferred range of the overall metal stoichiometric ratio of antimony: tin. Such a composition serves as a particularly effective metallurgical catalyst precursor composition in the method of the second aspect of the invention, and results in the formation of such an anode structure: having a particularly effective combination of efficiency for the chlorine evolution reaction and high durability providing a longer working life at low overpotentials.

[0123] Therefore, in particular, it is preferred in the method of the second aspect that the metallurgical catalyst precursor composition comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the overall metal stoichiometric ratio of cobalt: total antimony and tin is in the range of 20:80 to 80:20, and the overall metal stoichiometric ratio of antimony: tin is at most 1:10, preferably at most 1:20. More preferably, the metallurgical catalyst precursor composition comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the overall metal stoichiometric ratio of cobalt: total antimony and tin is in the range of 40:60 to 60:40, and the overall metal stoichiometric ratio of antimony: tin is at most 1:50, preferably at most 1:100. Most preferably, the metallurgical catalyst precursor composition comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the overall metal stoichiometric ratio of cobalt: total antimony and tin is 50:50, and the overall metal stoichiometric ratio of antimony: tin is at most 1:100, preferably 1:200.

[0124] These highly preferred embodiments of the metallurgical catalyst precursor compositions may further comprise the preferred embodiments of the above-described crystalline cobalt oxide particles, particularly consisting essentially of a cobalt oxide having the formula Co 3 O 4 The crystalline particles may more preferably also contain substantially ruthenium to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is present in the form of surface decoration on the crystalline particles. In this latter embodiment, the crystalline cobalt oxide particles in the metallurgical catalyst precursor composition may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.

[0125] In an alternative embodiment of the method of the second aspect, a base composition is applied directly to the substrate prior to step (b), the applied metallurgical base composition advantageously comprising Ru providing the overall metal stoichiometry of the composition. ≥0.3 (Sn+Ti) ≤0.7 The present invention is important that the ruthenium content of the applied base composition is at a level of 0.3 (corresponding to 30 atomic %) or more stoichiometrically relative to the tin and titanium present in the base composition. It has been found that when the ruthenium in the composition is at or above this level, the durability of the resulting structural base layer is greatly improved when applied according to the method of the second aspect. In addition, ruthenium contributes to the overall conductivity of the base structural composition.

[0126] In this regard, it is preferred that the composition applied prior to step (b) comprises a metal that provides an overall metal stoichiometry of Ru to the composition. 0.3(Sn+Ti) 0.7 This level of ruthenium is believed to be optimal in the applied base composition of this embodiment of the method of the present invention, resulting in a particularly efficient and durable anode structure.

[0127] The presence of a combination of tin and titanium in addition to ruthenium in the base composition results, through its application in the method of the second aspect, in the formation of a structural base layer having the desired morphology of aggregated particles and the absence of mud cracking behavior seen in other compositions comprising ruthenium and only titanium or tin. In this regard, a minimum ruthenium content of 30 atomic % relative to tin and titanium in the applied base composition also results in an enhanced formation of a network of aggregated particles in the morphology of the resulting structural base composition, without cracking behavior.

[0128] The presence of tin in combination with ruthenium and titanium in the applied base composition also contributes importantly to the improved long term durability of the anode prepared according to the second aspect and results in improved mechanical adhesion of the composite metallurgical layer to the anode substrate.

[0129] To optimize these advantages, it is preferred that tin and titanium are present in approximately equal amounts in the applied base composition. Thus, most preferably, in this embodiment, the base composition applied prior to step (b) comprises Ru to provide an overall metal stoichiometry of Ru to the applied base composition. 0.3 Sn 0.35 Ti 0.35 Compounds of ruthenium, tin and titanium in varying amounts.

[0130] In all of the above embodiments of the second aspect, although minor amounts of other metal compounds may be present in addition to the essential ruthenium, tin and titanium compounds, it is preferred that the base composition consists essentially of ruthenium, tin and titanium compounds, and more preferably, the base composition consists of ruthenium, tin and titanium compounds, preferably in amounts that provide an overall metal stoichiometry of Ru to the base composition. 0.3 (Sn+Ti) 0.7 , most preferably providing an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 .

[0131] The metallurgical catalyst precursor composition and, if used, the structural base composition used in the process of the first aspect can each be prepared from compounds known in the art for metal oxide catalyst preparation, which are mixed together in the presence of a process solvent in appropriate ratios in accordance with the teachings of the present invention. Although these compounds may include related metal oxide compounds where feasible, other compounds are generally used that allow better mixing or suspension and oxidation under subsequent heat treatment of the process to produce the desired metal oxide in situ.

[0132] Thus, it is preferred in the process of the second aspect that the compounds of ruthenium, tin, antimony and titanium present in the applied composition each comprise a compound other than an oxide compound; and wherein their heated application, subsequent drying and heat treatment in the process causes these compounds to thermally decompose into one or more of their respective metal oxides or mixed metal oxide compounds within the metallurgical layer of the final anode structure.

[0133] In this regard, the compounds of ruthenium, tin and titanium present in any base composition preferably comprise, more preferably consist of, their respective halide compounds and / or complexes with acetylacetone; the tin and antimony compounds in the metallurgical catalyst precursor composition preferably comprise, more preferably consist of, their respective halide compounds; and when ruthenium is present, it preferably comprises, more preferably consists of, one or more of its respective halide compounds or complexes thereof with acetylacetone. These compounds provide for suitable dispersion of the metals in the composition used in the process, and are subsequently converted to their respective oxides under the conditions of the process of the invention to produce the desired anode of the first aspect of the invention.

[0134] The starting composition for the process may additionally comprise other metal compounds as detailed under the first aspect which bring further advantages to the resulting anode.

[0135] Thus, the starting composition may additionally comprise at least one palladium compound in an amount providing a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition. Preferably, the starting catalyst precursor composition additionally comprises at least one palladium compound in an amount providing a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition.

[0136] The catalyst precursor composition may further comprise at least one copper compound, or at least one aluminum compound or at least one nickel compound, or more than one of these, in amounts to provide the catalyst precursor composition with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition, or more than one of these.

[0137] At least one of the starting process compositions may additionally comprise at least one iridium compound in an amount which provides a total iridium content of at most 15 atom %, preferably at most 10 atom %, based on the total metal atom content of the composition.

[0138] These additional metal species may be introduced via compounds which are conventionally used in the art for inclusion in metallurgical coatings.

[0139] In a further preferred embodiment, the catalyst precursor composition does not contain any titanium compounds, and the process of the second aspect produces a titanium-free catalyst composition having the attendant advantages mentioned above.

[0140] In the method of the present invention, as detailed in the first aspect of the present invention, the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.

[0141] In the process of the present invention, the metallurgical catalyst precursor composition applied in step (b) and, if present, any underlying metallurgical interlayer may be applied sequentially by coating techniques known in the art, such as brushing, roller coating or knife coating, spraying (by means such as electrospraying or pressure spraying), dipping and curtain coating. Where desired, thicker coatings may be applied by multiple-pass coating techniques on the underlying structure.

[0142] Preferably, each metallurgical composition is applied sequentially by brushing one or more passes on the underlying structure, or by spraying one or more passes on the underlying structure. However, other conventional techniques may also be used to apply one or more metallurgical compositions.

[0143] The third aspect of the present invention (chlorine electrolysis system)

[0144] In a third aspect, the present invention provides an electrolytic chlorine production system, comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect.

[0145] Fourth Aspect of the Invention (Electrolysis Method)

[0146] In a fourth aspect, the present invention provides an electrolytic method for catalyzing the precipitation of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect, wherein chlorine gas is precipitated from the aqueous solution at the anode.

[0147] In a preferred aspect of the electrolytic process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an alternative preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.

[0148] Working Example of the Invention

[0149] 1. Preparation Example

[0150] Preparation of Exemplary Starting Compositions for Use in the Methods of the Invention

[0151] 1.A An exemplary starting composition for this method is prepared from the following component compounds and liquids available in the art:

[0152] Crystalline solid compounds:

[0153] RuCl 3. xH 2 O (available as a commercial product from Sigma-Aldrich),

[0154] SnCl 4. 5H 2 O (available as a commercial product from Sigma-Aldrich),

[0155] SbCl 3 (available as a commercial product from Sigma-Aldrich),

[0156] PdCl 2 (available as a commercial product from Alfa Aesar),

[0157] Ru(acac) 3 (available as a commercial product from Sigma-Aldrich; wherein "acac" stands for acetylacetone), and

[0158] With the chemical formula Co 3 O 4 The crystalline cobalt oxide particles were synthesized as follows.

[0159] liquid:

[0160] 2-Propanol (also known as isopropanol, available as a commercial product from Alfa Aesar),

[0161] Deionized water,

[0162] TiCl 3 Solution (TiCl 3 Available as a commercial product from Sigma-Aldrich (Sigma-Aldrich) as a 12% solution in aqueous hydrochloric acid.

[0163] 1.B Preparation of the basic interlayer composition of the method

[0164] A preferred base interlayer composition for use in the method of forming a structural base composition of a composite metallurgical layer is prepared according to the following sequence, consisting essentially of compounds of ruthenium, tin and titanium, with an overall metal stoichiometry of Ru: 0.3 Sn 0.35 Ti 0.35 .

[0165] Add RuCl to the 70 mL vial. 3 .xH 2 O (207.6 mg; 1 mmol) and SnCl 4 .5H 2 O (409.4 mg; 1.17 mmol). These solid materials were dissolved in 2-propanol (17 mL) by vortexing until no metal precursor settled on standing. To the resulting solution was added 1.5 mL of TiCl by dropwise addition under mechanical stirring at 1,000 rpm. 3 Solution (12% TiCl 3 In addition, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours under ambient conditions with mechanical stirring at 1,000 rpm to produce a base composition for an alternative embodiment of the method of the present invention.

[0166] 1.C Preparation of the Further Interlayer Composition of the Method

[0167] A composition consisting essentially of ruthenium dioxide for use in the method of supplementing the optional interlayer is prepared according to the following sequence.

[0168] A solvent was prepared by mixing 2-propanol (38.7 mL) and deionized water (7.8 mL). 15.5 mL of the prepared solvent was then placed in a 70 mL vial, to which 115.8 mg (0.29 mmol) of Ru(acac) was added. 3 and an additional 2 ml of IPA. The solution thus prepared was then sonicated for 20 minutes to produce an interlayer composition for use in the method of the present invention.

[0169] 1.D Preparation of Metallurgical Catalyst Precursor Composition of the Method

[0170] A preferred catalyst precursor composition consisting essentially of crystalline particles of cobalt oxide is prepared according to the following sequence for use as the composition of the composite metallurgical layer-forming catalyst composition in this process.

[0171] a)Co 3 O 4 Synthesis of crystalline particles

[0172] Co(NO 3 ) 2 6H2 ZrO (170 g, 0.584 mol) was dissolved in ethanol (99.9%, 510 ml). 1-Heptanol (510 ml) was added to the mixture and the mixture was stirred for 5 minutes. The mixture was transferred to a pressure reactor and heated at 160°C for 7 hours. The resulting mixture was allowed to stand for 16 hours to cool to room temperature and allow the solid product to settle. The resulting supernatant was decanted and the solid product was washed three times with isopropanol (100 ml). Between each wash, the product was thoroughly mixed and then centrifuged at 8500 rpm for 1 hour. The supernatant was decanted and removed in each case. Isopropanol (IPA) was added to meet a solid content of 12 wt % (the amount of IPA added was calculated by the resulting density of the mixed solution). The resulting mixture was heated to 40°C with a mixture containing 0.5 mm ZrO. 2 The beads were ball milled at 2000 rpm at room temperature for 2 h to produce 12 wt% Co 3 O 4 Nanoparticle solution.

[0173] The Co synthesized above 3 O 4 The crystalline particles were sized by direct measurement of the diameter in transmission electron microscopy images and were found to be between 3 nm and 7 nm in diameter with a median diameter of 5 nm.

[0174] b) Preparation of metallurgical catalyst precursor composition

[0175] The solvent was prepared by mixing 2-propanol (38.7 mL) and deionized water (7.8 mL). 3 (44.7 mg; 0.20 mmol) was dissolved in the solvent by vortexing. 5 mL of the solution thus prepared was then diluted with an additional 45 mL of the solvent mixture to form a first "antimony solution". 15.5 mL of this antimony solution was then mixed with SnCl 4 .5H 2 O (457.8 mg; 1.31 mmol) was mixed under vortex to form an "antimony-tin solution".

[0176] PdCl 2 (4.8 mg; 0.027 mmol) was placed in a 70 ml vial, and then the prepared antimony-tin solution was poured into the vial. In addition, 1 ml of the Co prepared in a) above was added. 3 O 4 The crystalline particle solution (0.438 mmol) and 1 ml of 2-propanol were each added to the solution. Finally, the mixture was sonicated for 20 minutes to produce a precursor composition for the method of the present invention, which comprises Co in a solution of antimony and tin compounds. 3 O 4The crystalline particles contain 1 atomic % palladium, wherein the molar ratio of antimony:tin is 1:247 and the overall metal stoichiometric ratio of cobalt:total antimony and tin is 50:50. The catalytic anode of the present invention is prepared by the method of the present invention

[0177] Embodiment 1: Catalyst precursor composition is applied directly to the anode substrate

[0178] A titanium mesh was obtained as an anode substrate and, after cleaning, was heated to a temperature of 100°C using a hot plate. At this temperature, the composition from ID prepared above was applied to the hot substrate surface by brushing. The resulting coated sample was kept at 100°C for 1 minute, the substrate was turned over and the reverse side was coated again, the substrate was kept at 100°C for 1 minute. The coated sample was then transferred to a 500°C oven for 5 minutes. The coated sample was then transferred back to the hot plate at 100°C and the coating and heat treatment steps were repeated. This brushing of the substrate surface with this composition was repeated another four times, for a total of five brushings on the surface.

[0179] Embodiment 2: Interlayer composition is applied directly to the anode and covered with catalyst precursor composition

[0180] The method according to the second aspect of the invention The anode according to this embodiment of the first aspect of the invention is prepared as follows.

[0181] A titanium mesh was obtained as an anode substrate and, after cleaning, was heated to a temperature of 100° C. using a hot plate. At this temperature, the base composition from 1.B prepared above was applied to the hot substrate surface by brushing. The resulting coated sample was kept at 100° C. for 1 minute, the substrate was turned over and the reverse side was coated again, the substrate was kept at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven for 5 minutes. The coated sample was then transferred back to the hot plate at 100° C., and the coating and heat treatment steps were repeated. This brushing of the substrate surface with this composition was repeated another four times, for a total of five brushings on the surface.

[0182] The resulting structure was then further painted with the composition from 1.C prepared above in the same manner as described above, for a total of five passes on the surface. The resulting structure was thereafter further painted with the catalyst precursor composition from 1.D prepared above, for a total of 10 passes on the surface with this catalyst precursor composition. After these coating steps, the resulting coated structure was dried at the same temperature.

[0183] Then, the dried resultant structure was finally heat treated in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.

[0184] Embodiment 3: Anode substrate having been directly coated with a conventional dimensionally stable anode composition and then covered with a catalyst precursor composition

[0185] A commercially available anode structure pre-coated with a conventional dimensionally stable anode composition is thereafter coated with a ruthenium oxide interlayer prepared according to Section 1.C above, according to an application method similar to that used for Embodiment 2 above, and thereafter coated with a metallurgical catalyst precursor composition prepared according to Section 1.D above.

[0186] The result is an anode structure with a multilayer coating, in which the base layer is the dimensionally stable anode composition, the intermediate layer is ruthenium oxide and the surface layer is the metallurgical catalyst layer according to the invention.

[0187] 2. Performance Examples

[0188] The following experimental techniques were used to demonstrate the performance and advantages of the anode of the present invention.

[0189] Chlorine evolution reaction (CER) efficiency test:

[0190] The Faradaic efficiency of an electrolyser provides an important measure of the efficiency of the catalytic anode for the CER reaction.

[0191] An electrolytic cell was set up in which the counter electrode (cathode) and the working electrode (anode according to the invention) were configured as follows.

[0192] 5x 15cm 2 The Ti mesh counter electrode was etched with 2.0 M sulfuric acid at 60 °C for 1 hour until the etching solution turned light purple. The etched Ti mesh was then sonicated with 95% pure ethanol for 10 minutes several times. The rinsed Ti mesh was dried by blowing nitrogen. The dried counter electrode was then masked with silicon tape and plating tape to leave 5 x 5 cm 2 area.

[0193] The anode prepared according to the present invention was also masked with silicon tape and electroplating tape to leave a 1 x 5 cm 2 Masking the electrodes helps to focus the current into a confined area of ​​the electrode exposed to the electrolyte, thus increasing the current density and speeding up the test.

[0194] The electrolytic cell was assembled by attaching a masked counter electrode to one side of an electrode frame and a working electrode to the opposite side of the frame. At the bottom end of both electrodes, a portion of the frame maintained a gap of 5 mm between the electrodes.

[0195] The above test electrolyzer was configured and operated under the following conditions:

[0196] a) Pour 500 ml of 20 mM NaCl solution into a 500 ml beaker. Place the electrode unit assembled above in the beaker and connect two wires to the working electrode and the counter electrode respectively.

[0197] b) Stir the solution at 300 rpm using a magnetic stir bar. The connected potentiostat is then set at 40 mA / cm 2 The assay was run in chrono-potentiometry mode for 1 min.

[0198] c) After 1 minute of operation, the active chlorine concentration was measured and compared with the theoretical concentration obtained from the initial chloride ion concentration to determine the Faradaic efficiency (FE) of the electrolytic cell containing the working electrode (anode of the present invention).

[0199] Active chlorine concentration is measured by one of two interchangeable methods:

[0200] Active chlorine concentration measured by DPD colorimetry

[0201] In this method, the DPD vials were washed with DI water until initial testing confirmed the absence of residual active chlorine in the test vials.

[0202] After the electrolyzer was run for 1 minute, the solution was stirred at 600 rpm for 1 minute to make a completely uniform test solution. Then 1 ml of this well-mixed solution was diluted to 1 / 10 with 20 mM NaCl solution in a DPD vial to obtain a test solution volume of 10 ml. The DPD reagent was then added to the DPD vial and the vial was vortexed for 10 seconds. The active chlorine concentration was then measured with a DPD portable colorimeter and the Faraday efficiency (FE) was calculated by dividing the amount of active chlorine generated by the theoretical amount of active chlorine generated.

[0203] Determination of active chlorine content by iodometric titration

[0204] After the electrolyzer was run for 1 minute, the solution was stirred at 300 rpm to make a uniform solution. Then 1.6 grams of KI (potassium iodide) were added to the beaker containing the solution. After adding KI, the solution became light yellow. After adding 4 milliliters of glacial acetic acid to the solution, the solution became light orange. After 4 milliliters of starch solution were added to the beaker, the solution became dark blue. The dark blue solution was then titrated with 0.02N sodium thiosulfate until the solution became colorless, and the amount of active chlorine generated was estimated by the titration of the sodium thiosulfate added. The Faraday efficiency was calculated again by dividing the amount of active chlorine generated by the theoretical amount of active chlorine.

[0205] Chlorine evolution reaction (CER) life test:

[0206] The Faradaic efficiency of an electrolyser, measured regularly during long-term testing, provides important evidence of the lifetime of the catalytic anode and, therefore, the durability of the anode for CER reactions. A rapid increase in FE signifies degradation of the anode and indicates that it is approaching the end of its durability for CER reactions.

[0207] The electrolytic cell with counter and working electrodes was configured as described above. For experimental acceleration purposes, the working electrode (anode) was masked to 1 cm 2 To concentrate the current density. Masking was done by applying silicon tape, covered with plating tape. The top of the working electrode was also grounded back to the metal substrate before connection.

[0208] a) Pour 1 liter of 0.6 M NaCl solution into a beaker surrounded by a cooling jacket, which maintains the test solution at 15° C. After allowing the temperature to stabilize for 1 hour, place the electrode unit assembled above inside the beaker and connect two wires to the working electrode and the counter electrode, respectively.

[0209] b) Stir the solution at 300 rpm using a magnetic stir bar. The connected potentiostat is then set at 500 mA / cm2 under stirring conditions at 300 rpm. 2 The experiment was run in chrono-potentiometry mode until an increase of more than 12 V was recorded, at which point the result was taken as the duration of the experiment.

[0210] c) During operation, the potential of the electrolyzer is repeatedly measured and plotted over time to report the potential for the CER over the duration of the life test and to identify the degradation point where the potential increases rapidly and exceeds the useful life of the anode.

[0211] Mechanical adhesion test

[0212] The mechanical adhesion of the metallurgical surface layer of the anode is evaluated by the following method. A piece of 3M electroplating tape is placed on a part of the unshielded working electrode (tested anode) prepared as described in detail above. Apply slight pressure with a pipette head so that the tape is in close contact with the electrode surface of the coating without any effort. Then peel off the tape, and visually evaluate the extent to which the residue of the metallurgical coating is retained on the adhesive surface of the stripping tape, as a measure of the adhesion strength of the coating to the electrode substrate, the more residues on the removed tape indicate that the residual adhesion to the substrate is lower.

[0213] Acid stability test

[0214] Prepare a 5 wt% hydrochloric acid solution by diluting concentrated hydrochloric acid with deionized water to the required amount. Cut the anode to be tested into a size of 2 cm x 1 cm and place it in a 10 ml vial, to which 5 ml of 5% hydrochloric acid solution is added so that the anode sample is completely immersed. Observe the color of the sample and the acid solution over time.

[0215] 2.1 Performance of the catalyst composition of the present invention

[0216] The importance of catalyst chemical composition to performance is explained below.

[0217] 2.1(a) Including Tin and Antimony Oxide Matrix in Catalyst Composition

[0218] exist Figure 3 and 4 The advantageous presence of cobalt, tin and antimony in the specified stoichiometric ratios is shown in FIG. Similar anodes were prepared according to the Example of Embodiment 1 in Section 1 above, but using catalyst precursor compositions with varying tin and antimony contents as shown in the figure. In each case, life tests were performed and the (over)potentials were compared over time.

[0219] like Figure 3 It was demonstrated that the overall metal stoichiometric ratio of cobalt: antimony and tin in the catalyst precursor composition has an impact on the life of the anode, and anode structures made from catalyst precursor compositions wherein the ratio is in the range of 20:80 to 80:20, preferably 50:50, exhibit greatly improved durability in terms of maintaining low potential over a longer operating life. A 50:50 molar ratio provides the best performance in this regard.

[0220] like Figure 4 As demonstrated, for similar anodes prepared according to the Example of Embodiment 2 of Section 1 above, with varying antimony and tin compounds, amounts providing the catalyst precursor composition with an overall metal stoichiometry of antimony:tin of up to 1:20 exhibited a lifetime advantage relative to anodes having a ratio greater than 1:10. Figure 5 In the present invention, the CER efficiency as measured by the Faradaic efficiency (FE) using the method detailed earlier in this specification shows an increasing advantage at ratios of 1:20, 1:50, 1:100 and 1:200, the latter being the most efficient catalyst precursor composition, resulting in an anode with the highest efficiency.

[0221] 2.1(b) Including palladium oxide in the catalyst composition

[0222] In a further experiment, the anode was directly coated with a catalyst composition containing cobalt oxide particles, ruthenium oxide and oxides of tin and antimony according to the invention, and the effect of introducing palladium as a further component was evaluated. The results are shown in the table below, which demonstrates the efficiency improvement brought about by the preferred inclusion of a small amount of palladium in the catalyst composition.

[0223]

[0224] (Exposed anode area (5cm 2 )、1.17g / L NaCl concentration)

[0225] 2.1(c) Improvements provided by the catalyst composition in anode structures having a dimensionally stable anode interlayer

[0226] CER efficiency testing and CER life testing were conducted on a conventional anode coated with a dimensionally stable anode composition (Ru: 15.7, Ti: 11.93, Ir: 1.51 at % as measured by SEM / EDX at an accelerating voltage of 20 kV) in comparison with the same anode to which a ruthenium oxide interlayer had been applied according to Embodiment 3 in Section 1 above, followed by a modified version of the metallurgical catalyst composition. The results are shown in the following table:

[0227]

[0228] As shown in the results, adding a cobalt-based metallurgical catalyst layer and a ruthenium oxide intermediate layer to form the anode of the present invention results in a 16.1% improvement in CER efficiency compared to a conventional DSA-only catalyst layer; and the anode of the present invention has a 33% improvement in lifetime compared to conventional anodes.

Claims

1. A catalytic anode structure for an electrolytic chlorine production system comprising a conductive solid substrate having a conductive metallurgical catalyst layer coated on the surface of the substrate facing the electrolyte, the catalyst layer comprising a crystalline matrix of antimony and tin oxides consisting essentially of a metallurgical catalyst having the chemical formula Co 3 O 4 cobalt oxide crystalline particles composed of crystalline cobalt oxide; wherein the cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer; and wherein the overall metal stoichiometry of the total amount of cobalt: antimony and tin in the metallurgical catalyst layer is in the range of 2:1 to 9:

1.

2. An anode structure according to claim 1, wherein the antimony and tin compounds are present in amounts to provide the metallurgical catalyst layer with an overall metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:

100.

3. An anode structure according to claim 1 or claim 2, wherein the metallurgical catalyst layer further comprises one or more noble metals or compounds thereof, preferably ruthenium or an oxide thereof.

4. The anode structure of claim 3, wherein the cobalt oxide crystalline particles in the metallurgical catalyst layer substantially contain ruthenium or its oxide to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of the ruthenium being present in the form of surface decoration on the crystalline particles.

5. The anode structure of claim 4, wherein the crystalline cobalt oxide particles in the metallurgical catalyst layer further contain crystalline regions in which ruthenium is incorporated into the cobalt oxide lattice or has formed a mixed metal oxide with cobalt, or both.

6. Anode structure according to any one of claims 3 to 5, wherein the metallurgical catalyst layer comprises at least one palladium compound in an amount to provide the metallurgical catalyst layer with a total palladium content of at most 7 atomic %, preferably at most 3 atomic %, based on the total metal atomic content of the metallurgical catalyst layer.

7. The anode structure of any one of claims 3 to 6, wherein the metallurgical catalyst layer further comprises ruthenium oxide distributed throughout or substantially distributed throughout the catalyst layer.

8. An anode structure according to any one of claims 3 to 7, wherein the metallurgical catalyst layer additionally comprises iridium, in the form of its oxide or other catalytically active species, in an amount providing a total iridium content of at most 15 atomic %, preferably at most 5 atomic %, of the total metal atomic content of the metallurgical catalyst layer.

9. Anode structure according to any one of claims 1 to 8, wherein the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.

10. An anode structure according to any one of claims 1 to 9, wherein the metallurgical catalyst layer further comprises at least one copper compound in an amount such that the layer provides at most 10 atomic %, preferably at most 2 atomic %, of the total copper content of the metallurgical layer; or at least one aluminum compound in an amount such that the layer provides at most 30 atomic %, preferably at most 20 atomic % of the total aluminum content of the metallurgical layer; or at least one nickel compound in an amount such that the layer provides at most 15 atomic %, preferably at most 10 atomic % of the total nickel content of the total metal atomic content of the metallurgical catalyst layer, or more than one of these.

11. The anode structure according to any one of claims 1 to 10, wherein the metallurgical catalyst layer does not contain titanium or compounds thereof.

12. An anode structure according to any one of claims 1 to 11, wherein the anode structure consists of an electrically conductive solid substrate covered on its surface facing the electrolyte with an electrically conductive metallurgical catalyst layer according to any one of claims 1 to 11, the catalyst layer being directly adjacent to the substrate.

13. An anode structure according to any one of claims 1 to 11, wherein the anode structure comprises a conductive solid substrate covered on its surface facing the electrolyte with a metallurgical interlayer directly adjacent to the substrate; the interlayer is covered by a conductive metallurgical catalyst layer according to any one of claims 1 to 11.

14. The anode structure of claim 13, wherein the interlayer is a dimensionally stable anode composition.

15. An anode structure according to claim 13 or claim 14, wherein the interlayer comprises titanium or one or more compounds thereof, or tantalum or one or more compounds thereof, or both.

16. Anode structure according to any one of claims 13 to 15, wherein the interlayer comprises ruthenium or one or more compounds thereof, preferably also titanium or one or more compounds thereof.

17. An anode structure according to any one of claims 13 to 16, wherein the interlayer comprises iridium or one or more compounds thereof.

18. An anode structure according to any one of claims 13 to 17, wherein the titanium, tantalum, ruthenium or iridium compound, when present, comprises, preferably consists of, an oxide compound.

19. A method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps: a) preparing or obtaining a conductive solid substrate; b) applying to the surface of the substrate facing the electrolyte a conductive metallurgical catalyst precursor composition comprising a catalyst having a chemical formula of Co dispersed in a mixture of antimony and tin compounds 3 O 4 a composition of crystalline cobalt oxide particles composed of crystalline cobalt oxide ... wherein the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

20. A method according to claim 19, wherein during step (b) the substrate (a) is heated to a temperature in the range of 55-200°C and the resulting structure is thereafter dried at a temperature in said same range.

21. A method according to claim 20, wherein the substrate (a) is heated to a temperature of 100°C throughout step (b) and the resulting structure is thereafter dried at said temperature.

22. The method according to any one of claims 19 to 21, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.

23. The method according to any one of claims 19 to 22, wherein the heat treatment temperature is 500°C.

24. A method according to any one of claims 19 to 23, wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a ratio in the range of 85:15 by volume.

25. A method according to any one of claims 19 to 24, wherein each metallurgical composition applied in step (b) is applied sequentially by brushing on the underlying structure in one or more passes.

26. A method according to any one of claims 19 to 25, wherein each metallurgical composition applied in step (b) is applied sequentially by spraying one or more passes onto the underlying structure.

27. A process according to any one of claims 19 to 26, wherein the cobalt oxide crystalline particles in the metallurgical catalyst precursor composition further comprise ruthenium in an amount of up to 5 atomic % of ruthenium based on the total metal atomic content of the crystalline particles, at least some of the ruthenium being present in the form of a surface decoration on the crystalline particles.

28. The method of claim 27 wherein the crystalline cobalt oxide particles in the metallurgical catalyst precursor composition further contain crystalline regions in which some ruthenium has been incorporated into the crystal lattice of the cobalt oxide or has formed a mixed metal oxide with cobalt, or both.

29. The process of any one of claims 19 to 28, wherein the antimony and tin compounds are present in amounts to provide the metallurgical catalyst precursor composition with an overall metal stoichiometry of antimony:tin of at most 1:10, preferably at most 1:20; and most preferably 1:

200.

30. A process according to any one of claims 19 to 29 wherein the metallurgical catalyst precursor composition additionally comprises at least one palladium compound in an amount to provide the composition with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the composition.

31. A process according to any one of claims 19 to 30, wherein the compounds of tin and antimony in the metallurgical catalyst precursor composition each comprise a compound other than an oxide compound; and wherein their application of heat in step (b), followed by drying and heat treatment causes these compounds to thermally decompose into one or more of their respective metal oxides or mixed metal oxide compounds within the metallurgical catalyst layer of the final anode structure.

32. A process according to claim 31 wherein the tin and antimony compounds, when present, initially comprise, preferably consist of, their respective halide or sulphate compounds.

33. A process according to any one of claims 19 to 32, wherein the metallurgical catalyst precursor composition further comprises at least one copper compound, or at least one aluminum compound or at least one nickel compound, or more than one of these, in amounts to provide the composition with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition, or more than one of these.

34. A process according to any one of claims 19 to 33, wherein the metallurgical catalyst precursor composition additionally comprises at least one iridium compound in an amount which provides a total iridium content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition.

35. A method according to any one of claims 19 to 34, wherein the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.

36. A method according to any one of claims 19 to 35, wherein in step (b) the metallurgical catalyst precursor composition is applied directly to the electrolyte-facing surface of the substrate.

37. A method according to any one of claims 19 to 36, wherein prior to step (b), a metallurgical base composition is applied directly to the electrolyte-facing surface of the substrate to form a metallurgical interlayer directly adjacent to the substrate surface; and in step (b), the metallurgical catalyst precursor composition is applied to the outer surface of the metallurgical interlayer.

38. An electrolytic chlorine production system comprising the electrolytic anode structure according to any one of claims 1 to 18 or the electrolytic anode structure obtainable by the method according to any one of claims 19 to 37.

39. An electrolytic process for the precipitation of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising an electrolytic anode structure according to any one of claims 1 to 18 or an electrolytic anode structure obtainable by a process according to any one of claims 19 to 37, wherein chlorine gas is precipitated from the aqueous solution at the anode.

40. The electrolysis process of claim 39, wherein chlorine evolution from the aqueous solution is promoted by the catalytic action of the metallurgical catalyst layer covering the surface of the anode.

41. An electrolysis process according to claim 39 or 40, wherein the chlorine evolved by the process is used as a biocide to disinfect water.

42. The electrolysis method according to claim 41, wherein the chlorine gas is used to disinfect ballast water or industrial wastewater.

43. An electrolytic process according to claim 39 or 40, wherein the process is a chlor-alkali process for the generation and recovery of chlorine gas.